Value added tax on electronic services: an explorative study on the current regulations prescribing electronic services and the proposed amendments as at 01 October 2018 - Khulu, Ntombifuthi Valerie (Department of Finance and Tax, 2020)
Value-Added Tax (VAT) was introduced in South Africa (“SA”) on 29th September 1991 to replace GST (General Sales Tax) as an indirect system of taxation. It is levied in terms of the Value-Added Tax Act 89 of 1991. The Commissioner of the South African Revenue Service (SARS) is a mandated collector of all tax that is legally payable. SARS has a duty to ensure that the collection of tax is efficient and effective. VAT is a transaction and consumption-based tax that is triggered upon the consumption of goods and services in South Africa. South Africa operates a destination-based VAT system, which means that exports are zero-rated, and imports are subject to VAT at the standard rate of 15 per cent. The upshot of the destination-based VAT system is that it is designed to tax the consumption (in economic parlance) that takes place in South Africa (SA). For the purposes of VAT, revenue loss as a result of cross border supply of goods is insignificant in comparison to revenue loss experienced in the cross-border supply of services supplied via electronic means. This is due to the tangible nature of goods which would be required to be channelled through the border and/or customs, which are generally strictly controlled areas. Such goods could be subject to domestic tax (including VAT), thereby limiting the trade distortions as the foreign supplier will be put in the same tax position as the local supplier. However, all of this will be dependent on domestic legislation and value thresholds in a particular jurisdiction. In the instance of cross border supplies of services supplied electronically, there is increased exposure or risks to trade distortions since these are provided via the internet or through other forms of electronic agents or communication methods. These supplies do not have to physically pass through the border or customs, thereby limiting the control and monitoring of tax authorities. Imported services/reverse charge mechanism is where services supplied by non-residents are taxed within a taxing jurisdiction. This means that a resident of South Africa must account for VAT on services acquired from a non-resident or a person who carries on a business outside of South Africa, to the extent that such services are not used in the furtherance of taxable supplies. Essentially, the responsibility for the collection of tax does not lie with the non- resident but the person who imported the goods or services into South Africa. This is known as the reverse charged mechanism and is applied with respect to imported services acquired from non-resident businesses, consumed in South Africa and not for the furtherance of taxable supplies. In order to level the playground between foreign and local suppliers, the legislature introduced new rules governing the supply of electronic services by a foreign supplier to South Africa. This was done to eradicate the incorrect interpretation & application of the provisions governing imported services. In the 2018 National Budget Speech, released on 21 February 2018, the Minister of Finance announced that the regulation defining “electronic services” for VAT purposes would be updated. This resulted in an amended draft regulation being published on the same date. On 24 October 2018, the Minister of Finance presented the Medium-Term Budget Policy Statement which was accompanied by the Amendment of Revenue Laws Bill 37 of 2018 (“the Bill). Amongst those amendments contained in the Bill was the changes in the VAT treatment of the supply of electronic services (“e-services”) in South Africa. These amendments and the revised e-services regulations are due to take effect on 1 April 2019. The objective of this paper is to discuss to what extent the SA regulations are in line with regulations introduced in the Ottawa Taxation Framework. This paper will also discuss the Amendment of Revenue Laws Bill 37 of 2018 considering electronic services. Lastly, the EU, New Zealand and Australia’s frameworks will be looked at to establish if they have also amended their local VAT/GST legislation considering the Ottawa Taxation Framework. New Zealand, Australia and EU were chosen as target jurisdictions of comparison because they are more developed than South Africa. Furthermore, South Africa has economic relations with Australia and some countries which form part of the European Union. It is also understood that Australia’s GST and South Africa’s VAT are similar in terms of certain aspects. Collectively, South Africa’s VAT and Australia’s GST were both based on the New Zealand’s GST model. This paper finds that the recent amendments by the National Treasury are broad and do not conform to the Ottawa Taxation Framework. The paper also finds that the regulations looks fine on paper, but the implementation thereof will be challenging to both SARS and the VAT vendors. The paper suggests that the National Treasury should look at what countries i.e. New Zealand have done to address the challenge of taxing 'electronic services’ to ensure that the SA VAT legislation is amended in accordance with the suggested guidelines.